VD_FINDINFO HC / 2014 / 106 vom 16. Januar 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, DÉCISION SUR FRAIS, HONORAIRES, AGENT D'AFFAIRES | 95 al. 1 CPC (CH), 3 al. 1 TDC, 3 al. 2 TDC, 3 TDC